Comparison of Antimicrobial Activity of Allium sativum Cloves from China and Taşköprü, Turkey - Ali Yetgin; Kerem Canlı; Ergin Murat Altuner (Advances in Pharmacological Sciences)
In this study, antimicrobial activities of two different samples of Allium sativum L. from Turkey (TR) (Taşköprü, Kastamonu, Turkey) and China (CN) were determined. A broad spectrum of Gram-negative and Gram-positive bacteria (17 bacteria) including species of Bacillus, Enterobacter, Enterococcus, Escherichia, Klebsiella, Listeria, Pseudomonas, Salmonella, and Staphylococcus were used for testing antibacterial activity. In addition, antifungal activity against Candida albicans was also investigated. Antimicrobial activity was tested by using 3 different processes (chopping, freezing, and slicing by the disk diffusion method). The results showed that TR garlic presented more antimicrobial activity than CN garlic. Mechanism of activity of CN garlic could be proposed to be different from that of TR garlic.